GEMILANG (BALANCED NUTRITION FOR A BRILLIANT GENERATION): EDUCATION AND EMPOWERMENT OF PREGNANT WOMEN AND TODDLERS IN STUNTING PREVENTION BASED ON LOCAL FOOD - Charisma, Acivrida; Octifani, Amellya; Anwari, Farida; Dewi Nur Aini, Jessica; Cahyani Putri, Sintia; Charrisa Amelinda, Nora (Community Service Journal of Indonesia, 2025)
Stunting, or the condition of growth failure in children under five, is caused by chronic malnutrition that occurs from pregnancy until the child is two years old. Children experiencing stunting have a height below the standard for their age and are at risk of cognitive, motor, and immune system impairments. The community service program GEMILANG (Balanced Nutrition for a Brilliant Generation) was carried out in Kesamben Wetan Village, Driyorejo District, Gresik Regency, activity was conducted from Agustus 2025 with the aim of improving the knowledge, skills, and nutritional awareness of pregnant women, mothers of toddlers, and posyandu (integrated health post) cadres in stunting prevention based on local food. Activities included education on balanced nutrition, introduction to the potential of local food sources, training on nutritious food processing such as moringa leaf pudding, and strengthening the capacity of posyandu cadres in monitoring the nutritional status of toddlers. The implementation method used a participatory approach through interactive lectures, group discussions, demonstrations, and hands-on practice. Evaluation was conducted using pre-tests and post-tests as well as participant practice observations. The results showed an average knowledge increase of 33–35%, 90% of participants were able to practice the recipes at home, and 38% began utilizing their yards to grow vegetables or moringa leaves. In addition, there was a 20% increase in toddler attendance at posyandu after the program’s implementation. In conclusion, an educational approach combined with local food processing practices proved effective in improving nutrition literacy and encouraging changes in family consumption behavior. This program has the potential to become a model for community empowerment based on local potential to support sustainable stunting reduction efforts.